Beyond Global Youth Culture: A Cross-National Comparison of YouTube Usage across the United States, Saudi Arabia, and Taiwan. Issue 3 (2nd October 2021) - Abuljadail, Mohammad; Harmon, Michael; Ha, Louisa
ABSTRACT: This paper examines the differences and similarities among three major YouTube markets (U.S.A., Saudi Arabia, and Taiwan) that are culturally very different to test the media globalization and global youth culture thesis and how national cultural values affect YouTube use. Hofstede's cultural dimension framework was employed to explain the cultural differences in affecting the use of video genres and activities on YouTube. We found more differences than similarities among the U.S., Saudi Arabia, and Taiwan in program genre viewership and activities on YouTubes. Gender difference in program genre viewership was largest in Saudi Arabia with highest power distance and second highest in masculinity. Saudi Arabia also scored highest in engagement activities on YouTube. The results of this study enable media managers and global marketers to develop strategies to provide online video services and utilize YouTube for promotion and underscore the importance of developing recommendation algorithms and other popularity indexes such as the trending page.